Micro-Nano Bubbles: A New Field of Eco-Friendly Cleaning - Nan Guan; Yao Wang; Jun Hu; Lijuan Zhang (Nanomaterials)
Due to increasing public awareness of environmental concerns and stricter cleaning process requirements, traditional cleaning technologies characterized by high pollution, excessive energy consumption, and substantial damage are insufficient to meet contemporary demands. There is an urgent need for efficient, low-damage, and environmentally friendly cleaning technologies. In recent years, the rapid advancement of micro-nano bubbles (MNBs), which exhibit unique physicochemical properties, have emerged as a promising solution for green cleaning applications. This review begins with an overview of the benefits of MNBs in cleaning processes, followed by an in-depth analysis of the factors influencing their cleaning effectiveness as well as the possible mechanisms involved. Additionally, the producing and application of MNBs across various cleaning scenarios are summarized. Finally, prospects for their development are discussed. Research and advancements in MNB preparation technologies are expected to boost their applicability and commercialization in a greater variety of cleaning contexts in the future.